Upaya Guru Bimbingan dan Konseling dalam Mengatasi Perilaku Maladaptif dengan Layanan Konseling Kelompok - Satriya Tubagus; Jarkawi Jarkawi; Farial Farial (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2020)
This study aims to describe 1). forms of maladaptive behavior of students at SMPN 14 Banjarmasin, 2). factors - factors that affect students 'maladaptive behavior at SMPN 14 Banjarmasin, 3). Teacher guidance and counseling efforts in overcoming students' maladaptive behavior at SMPN 14 Banjarmasin. The method used in this study is a qualitative method with a descriptive approach. Data sources in this study are: Bk Teachers, Homeroom Teachers, and Students of SMPN 14 Banjarmasin. Data collection techniques in this study used observation, interviews, and documentation. The validity of the data in this study uses triangulation and extension of participation. While the analysis of the data used in this study is the analysis of making conclusions from the entire discussion. The results of this study indicate that the maldaptive behavior of SMPN 14 Banjarmasin students in general is often done that is ditching, making a fuss in the classroom, and bullying friends. Factors causing the maladaptive behavior of students at SMPN 14 Banjarmasin are, factors of weak self-control, family factors, and environmental factors or peers who are not good and do not support in adjusting to the environment. The efforts that have been done by BK Teachers in overcoming maladaptive behavior of SMPN 14 Banjarmasin students are identifying problems, collecting student data and student backgrounds, collaborating with other teachers and parents in solving students' problems at school, giving reprimands or punishment as well as advice its nature of educating and educating students themselves. Keywords: Guidance and Counseling Teachers, Maladaptive Behavior